Journal - Braine, Emily, 1844- (1854)
The journal was written by Emily Braine, who sailed from Liverpool on 23rd December 1854 on board the ship "Eagle". She and her grandmother arrived in Melbourne on the 5th of April 1855. The journal describes the journey and her grandmother's illness.
Manuscript reference: NLA MS 8413.
Emily Braine sailed from Liverpool to Australia with her grandmother.
Keywords: Braine, Emily, -- 1844- -- Diaries; Eagle (Ship); Voyages and travels